Penerapan media high impact imagery booklet untuk panduan pembuatan menu gizi seimbang bagi ibu balita - Alma, Lucky Radita; Ulfa, Nurnaningsih Heryah; Rahmawati, Indana Tri; Syahrani, Rizky Aura; Rusalam, Grevilla Deva Salsabela; Maulida, Nalaina Izzaty; Nuraziizah, Nida’a Astie; Novitasari, Zahra Rizki; Amanda, Dian; Maulida, Marshanda Rachma; Wardani, Fransisca Puspita (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Malnutrition in toddlers, particularly stunting, remains a serious health problem in Indonesia. Data from the 2018 Basic Health Research (Riskesdas) showed that 30.8% of toddlers experienced stunting, while 6.2% of babies were born with low birth weight. Causal factors stem not only from economic conditions but also from parents' lack of knowledge about balanced nutrition, appropriate parenting patterns, and the persistence of myths and misconceptions. To address this problem, effective educational media are needed, one of which is through a communicative, visual-based booklet. Purpose: To develop and test the application of a high-impact imagery booklet as a guide to creating balanced nutritional menus for mothers of toddlers. Method: This research and development (R&D) study used the ADDIE model, encompassing the stages of Analysis, Design, Development, Implementation, and Evaluation. The pre-experimental research design included a pre-test and post-test on 65 mothers of toddlers. Data analysis was conducted to assess the increase in participants' knowledge regarding child nutrition following the HII-Book intervention. Results: The resulting product, the HII-Book, contains a balanced nutrition guide, sample menus, and engaging illustrations. The trial showed an increase in knowledge among mothers of toddlers, with 57.9% of mothers in the good category before the intervention. After the intervention, the good category increased to 78%. Participants also responded positively to the HII-Book-based outreach activities, nutrition consultations, and cooking demonstrations. Conclusion: The HII-Book educational media has proven effective in increasing mothers of toddlers' knowledge and understanding of balanced nutrition. This program can serve as a reference for public health interventions to prevent stunting and support the implementation of healthier parenting patterns within the family environment. Keywords: Balanced Nutrition Menu; High Impact Imagery Booklet (HII-Book); Mothers; Toddlers. Pendahuluan: Kekurangan gizi pada anak balita, khususnya stunting, masih menjadi masalah kesehatan serius di Indonesia. Data Riset Kesehatan Dasar (Riskesdas) 2018, menunjukkan 30.8% balita mengalami stunting, sementara 6.2% bayi lahir dengan berat badan rendah. Faktor penyebab tidak hanya berasal dari kondisi ekonomi, tetapi juga kurangnya pengetahuan orang tua mengenai gizi seimbang, pola asuh yang tepat, serta masih adanya mitos dan kepercayaan keliru. Untuk mengatasi masalah ini, diperlukan media edukasi yang efektif, salah satunya melalui booklet berbasis visual yang komunikatif. Tujuan: Untuk mengembangkan dan menguji penerapan media high impact imagery booklet untuk panduan pembuatan menu gizi seimbang bagi ibu balita. Metode: Penelitian Research and Development (R&D) dengan model ADDIE, meliputi tahap Analyze, Design, Development, Implementation, dan Evaluation. Desain penelitian pre-eksperimental dilakukan dengan pre-test dan post-test pada 65 ibu balita. Data analisis untuk menilai peningkatan pengetahuan peserta terkait gizi anak setelah intervensi dengan HII-Book. Hasil: Produk yang dihasilkan berupa HII-Book berisi panduan gizi seimbang, menu contoh, dan ilustrasi menarik. Uji coba menunjukkan peningkatan pengetahuan ibu balita, sebelum intervensi termasuk dalam kategori baik sebesar 57.9%. Setelah intervensi, kategori baik meningkat menjadi 78.%. Respon peserta juga positif terhadap kegiatan sosialisasi, konsultasi gizi, dan demo masak berbasis HII-Book. Simpulan: Media edukasi HII-Book terbukti efektif meningkatkan pengetahuan dan pemahaman ibu balita tentang gizi seimbang. Program ini dapat menjadi acuan intervensi kesehatan masyarakat untuk pencegahan stunting serta mendukung penerapan pola asuh yang lebih sehat di lingkungan keluarga. Kata Kunci: Balita; Ibu; High Impact Imagery Booklet (HII-Book); Menu Gizi Seimbang.